Determinación del porcentaje de goma garrofín y ácido acético para efecto estabilizante en salsa picante de piña - Loor Sabando, Anthony Josué (2021)
In the present investigation, the stability of a spicy pineapple sauce was evaluated with the application of two factors: A (5 % and 10 % acetic acid) and B (locust bean gum in concentrations of 0,4 %, 0,6 % and 0,8 %). A completely randomized design (DCA) was used in a bifactorial AxB arrangement with six treatments. The variables pH (potentiometer), consistency (Bostwick consistometer), syneresis (centrifugation) were evaluated and it was also complemented with a sensory analysis (affective test). It was determined that the T4 treatment (10 % acetic acid and 0,4 % locust bean gum) had greater stability. The treatment with the highest acceptance was T6 (10 % acetic acid and 0,8 % locust bean gum). The stability of the pineapple hot sauce was influenced by the different percentages of locust bean gum and acetic acid used in the present investigation.